Polypeptides and proteins that influence beer foam quality and analytical methods used in their study - Isabel M P L V Ferreira (2006)
POLYPEPTIDES AND PROTEINS THAT INFLUENCE BEER FOAM QUALITY AND ANALYTICAL METHODS USED IN THEIR STUDY A review of polypeptides and proteins that influence, direct or indirectly, beer foam quality, as well as the most relevant analytical methods used in their study, are presented. Protein Z, LTP1 and hordein/glutelin fragments originated from malt have a direct influence on beer foam quality. Other proteins, like malt hordeins and albumins and wheat puroindolines, are, to some degree, also important for beer foam quality. Protein hydrophobicity is pointed out as a key parameter to enhance foam quality. Electrophoretic, chromatographic and immunological analytical methods are currently used to study polypeptides and proteins present in barley, malt, wort, beer, and foam. Best results are obtained when combinations of these methods are applied.